Theoretical design of innovative cold formed steel beam sections - Dar, M. Adil; Ashish, Deepankar K.; Dar, A. R. (International Journal of Scientific World, 2015)
In today’s world, the construction industry both structural and non-structural elements are fabricated from thin gauges of steel sheets. These thin walled sections are being used as columns, beams, joists, studs, floor decking, built-up sections and other components for lightly loaded structures. Unlike hot rolled sections, the design of Cold-Formed Steel (CFS) section for beam is predominantly controlled by various buckling modes of failure, thereby drastically reducing their load carrying capacity. Hence there is an urgent need in the CFS industry to look beyond the conventional CFS beam sections and investigate newly proposed innovative CFS beam sections, which seem to prove structurally much more efficient. Prior to any experimental investigation of innovative beam sections, there is a need to carry out theoretical design using some of the most appropriate available methods applicable to the case under consideration. This paper focuses on such theoretical designs for various innovative sections using available analytical design tools together with appropriate codal guidelines.